Pharmacokinetic Study of Oral 14C-Radiolabeled Hyzetimibe, A New Cholesterol Absorption Inhibitor - Jianwei Liao; Jianwei Liao; Xin Wang; Zhenyu Li; Dongsheng Ouyang; Dongsheng Ouyang; Dongsheng Ouyang (Frontiers Media S.A., 2021)
Background and objectives: Hyzetimibe is a candidate drug being investigated as the second-in-class cholesterol absorption inhibitor; it lowers plasma levels of low-density lipoprotein cholesterol (LDL-C) by blocking the Niemann-Pick C1-like 1 protein, a transporter mainly expressed in the intestine that allows dietary cholesterol to enter the body from the intestinal lumen. Previous studies on the metabolism of hyzetimibe in healthy volunteers were not enough to show the biotransformation and excretion pathway; in particular, whether hyzetimibe maintains pharmacological action for duration sufficient to pass through the hepatic-intestinal circulation remains unknown. Furthermore, it remains unclear whether the differences between the chemical structures of ezetimibe and hyzetimibe would result in different pharmacokinetic characteristics. Given that the molecular target is in the intestine and the substantial hepatic-intestinal circulation is a metabolic characteristic of the drug, a study of hyzetimibe as an oral 14C-radiolabeled drug, compared with routinely metabolized drugs, would play an important role in uncovering pharmacokinetic details.Methods: After an overnight fast and before taking medication, six healthy male volunteers swallowed an investigational product suspension containing 20 mg/∼100 μCi of 14C-labeled hyzetimibe as a single dose. Whole-blood, plasma, urine, and fecal samples were collected, and hyzetimibe and its metabolites were measured. Pharmacokinetic variables of hyzetimibe and its metabolites were calculated and statistically analyzed according to obtained concentration data. Safety data were collected throughout the study.Results: The major metabolite detected in plasma was hyzetimibe-glucuronide, which accounted for 97.2% of the total plasma radioactivity. The mean cumulative excretion of total radioactivity of the dose was 16.39% in urine and 76.90% in feces. Unchanged drug and hyzetimibe-glucuronide were identified as the major components in the feces and the urine, respectively. The main metabolic conversions of hyzetimibe were glucuronidation (M1), mono-oxidation (M4), and mono-oxidation with additional sulfonation (M7). Hyzetimibe was considered generally safe and well tolerated.Conclusion: This study of 14C-radiolabeled hyzetimibe provides a full profile of the biotransformation and excretion routes of hyzetimibe to improve the understanding of the pharmacokinetic characteristics of hyzetimibe. The changed hydroxyl group in the hyzetimibe structure made it easier for that drug, compared with ezetimibe, to combine with glucuronic acid and subsequently increased the urinary excretion of hyzetimibe vs. ezetimibe. These differences highlight the need to investigate in more detail the different pharmacokinetic impacts on the efficacy and safety of hyzetimibe and ezetimibe.